2019
DOI: 10.4012/dmj.2018-078
|View full text |Cite
|
Sign up to set email alerts
|

Effect of airborne-particle abrasion and, acid and alkaline treatments on shear bond strength of dental zirconia

Abstract: The surface roughness, morphology and shear bond strength (SBS) of dental zirconia using three different surface treatment techniques were evaluated. Three groups of sintered zirconia blocks were treated as follow, 1) Airborne-particle abrasion (APA) group (G1-APA), 50-µm Al2O3; 2) APA and 9% hydrofluoric acid etching (G2-HF); 3) APA and Sodium Hydroxide (G3-NaOH). The specimens were evaluated for roughness [atomic force microscope (AFM)], morphology [Scanning Electron Microscope (SEM)] and for SBS in the univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 23 publications
(43 reference statements)
0
10
1
Order By: Relevance
“…Chemomechanical retention is required for a stable bond between ceramic and composite resin. Different surface treatments have been proposed to enhance bonding to zirconia, such as sandblasting, tribochemical silicoating, and laser irradiation [ 1 , 2 , 10 , 11 ]. Sandblasting creates a porous surface and increases the bonding surface area and micromechanical retention [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemomechanical retention is required for a stable bond between ceramic and composite resin. Different surface treatments have been proposed to enhance bonding to zirconia, such as sandblasting, tribochemical silicoating, and laser irradiation [ 1 , 2 , 10 , 11 ]. Sandblasting creates a porous surface and increases the bonding surface area and micromechanical retention [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chemical surface treatments have also been suggested along with mechanical surface treatments to further enhance the bond strength to zirconia [ 10 , 12 , 13 ] such as application of bonding agents containing hydrophobic phosphate monomers, e.g., 10-methacryloyloxydecyldihydrogen¬phosphate (10-MDP) [ 8 , 10 , 13 , 14 ]. It has a hydrophobic methacrylate group at one end, which can bond to methacrylate-based restorations and cements, and has a polar phosphate group at the other end, which can bond to zirconia [ 1 , 10 , 13 , 15 ]. Primers containing 10-MDP create a reactive surface between zirconia and composite resin and enhance the μ SBS of zirconia to composite [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, zirconia ceramics do not contain silica components, and surface treatment with hydrofluoric acid and silane coupling agents application of zirconia ceramics is not a well-established method to achieve durable adhesion resin-based materials (Valente et al, 2020). Therefore, achieving the ideal bonding effect of zirconia is a significant problem that urgently needs to be solved in oral clinics (Flores-Ferreyra et al, 2019). Studies have shown that zirconia includes three crystal phases: monoclinic, tetragonal and cubic phases (Sriamporn et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Ceramic, a commonly used prosthetic material in stomatology, has very good biocompatibility, excellent corrosion resistance and wear resistance 1 . It has been currently recognised as the most realistic dental restoration material due to its prominent aesthetic performance 2 .…”
Section: Introductionmentioning
confidence: 99%